Diyanet İşleri Başkanlığı ve İslamiçi Dini Gruplarla (Mezhep ve Tarikatlar) İlişkileri - Kutlu, Sönmez (Dinî araştırmalar, 2009)
In this article, aim and functions of The Presidency of Religious Affairs has been discussed. Besides, it has been given place to discussion of laicism, the representation of Alouite sect- the Bektashi order in The Presidency of Religious Affairs, giving share from budget to Alouite sect